The Role of Digital Competence, Psychological Flexibility, and Career Resilience in the Digital Era - Tomo Hardiyanto; Ardian Saputra (JOB: Journal of Organizational Behavior, 2025)
This paper presents a comprehensive literature review exploring the critical interplay among digital competence, psychological flexibility, and career resilience within the evolving digital era. Prompted by the rapid adoption of digital technologies and recent global disruptions, the study posits that these three constructs are indispensable for individual and organizational success. The review systematically synthesizes existing academic literature, confirming that digital competence, encompassing a broad range of knowledge, skills, and attitudes, is a core requirement for navigating modern professional life. Simultaneously, psychological flexibility emerges as a vital intrapersonal resource, enabling individuals to adapt to change, manage stressors, and align actions with values. Both digital competence and psychological flexibility are shown to critically underpin career resilience, defined as the ability to adapt, recover, and thrive amidst career challenges. The key finding emphasizes a synergistic relationship where the combined effect of digital proficiency and a resilient, flexible mindset empowers individuals to effectively manage technological disruptions and thrive in dynamic work environments. Theoretical implications suggest an expansion of career development theories to integrate these constructs, proposing a "digital career resilience" framework. Practically, the study highlights the need for continuous digital skill development and the cultivation of psychological flexibility practices for individuals, and integrated training programs for organizations and educators. While acknowledging limitations inherent in a literature review, the paper outlines future research directions, including longitudinal studies and empirical validations, to further enrich the understanding of sustained career success in the digital age. Keywords: Digital Competence, Psychological flexibility, Career resilience